The Effects of Leniency on Cartel Pricing - Harold Houba; Evgenia Motchenkova; Quan Wen (Tinbergen Institute, 2014)
We analyze how leniency affects cartel pricing in an infinitely-repeated oligopoly model where the fine rates are linked to illegal gains and detection probabilities depend on the degree of collusion. A novel aspect of this study is that we focus on the worst possible outcome. We investigate the maximal cartel price, the largest price for which the conditions for sustainability hold. We analyze how the maximal cartel price supported by different cartel strategies adjusts in response to the introduction of (ex-ante and ex-post) leniency programs. We disentangle the effects of traditional antitrust enforcement, leniency, and cartel strategies on the maximal cartel price. Ex-ante leniency cannot reduce the maximal cartel price below the price under antitrust without leniency. On the other hand, for ex-post leniency, improvement is possible and granting full immunity to single-reporting firms achieves the largest reduction in the maximal cartel price. To reduce adverse effects under both leniency programs, fine reductions to multiple-reporting firms should be moderate or absent. Finally, ex-post leniency should provide less generous fine reductions to multiple-reporting firms, which is supported by the current practice in the US and the EU.
Keywords: L41; K21; C72; 330; Cartel; Antitrust; Competition Policy; Leniency Program; Self-reporting; Repeated Game